Using the Tools of Informal Science Education to Connect Science and the Public - April Killikelly (American Society for Microbiology, 2018)
Traditional modes of communication within the scientific community, including presentation of data at conferences and in peer-reviewed publications, use technical jargon that limits public engagement. While altering word choice is an important method for increasing public engagement, the data itself may not be enough. For example, communicating the lack of evidence that vaccines cause autism did not convince many reluctant parents to vaccinate their kids (Nyhan, Reifler, Richey, Freed, Pediatrics 133:e835–e842, 2014). To address this gap between the scientific community and the public, many journals are adopting open-access policies and publishing lay-abstracts. Meanwhile, “meet a scientist” programs are creating opportunities for scientists to engage with the public in person. However, these programs may not be as effective as they could be. Many scientists still subscribe to an information-deficit model in which “the data speaks for itself.” Alternative tools that go beyond the data are needed. Here, I present three tools to create connections between the public and science: 3-D objects, games, and storytelling. These multidimensional and multisensory methods do more than promote understanding of scientific data; they may also be used to convey science as a verb and as an essential viewpoint in the human struggle for understanding.